Composite component manufacturing method and composite component

Modifying the surface of the aluminum member by sandblasting and surface hydroxide process has solved the problem of insufficient joint strength in the prior art, and achieved better joint strength and anchoring effect.

CN111571916BActive Publication Date: 2025-03-28THE UNIV OF TOKYO +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202010086551.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-02-15
Filing Date
2020-02-11
Publication Date
2025-03-28
Estimated Expiration
2040-02-11

AI Technical Summary

Technical Problem

In the prior art, when manufacturing composite members of aluminum members and resin members, it is difficult to effectively improve the bonding strength, especially because acute angle protrusions formed by sandblasting may become the starting point for the breaking of the resin member.

Method used

The sandblasting process is used to form a concave and convex surface, and then the surface of the aluminum member is modified into aluminum hydroxide through the surface hydroxide process, and the acute angle protrusion is rounded, and the resin member is directly bonded to the modified surface.

Benefits of technology

The acute angle protrusions are removed through the surface hydroxide process to form chemical bonds and pore structures, which significantly improves the bonding strength and anchoring effect of the composite member.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111571916B_ABST
    Figure CN111571916B_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing a composite component having excellent bonding strength. The method for manufacturing a composite component in which an aluminum component and a resin component are bonded comprises the following steps: a sandblasting step of sandblasting the surface of the aluminum component; a surface hydrogen oxidation step of using at least one of heat and plasma to react the surface of the aluminum component after sandblasting with water to modify the surface of the aluminum component into aluminum hydroxide; and a bonding step of directly bonding the resin component to the surface of the aluminum component modified into aluminum hydroxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for manufacturing a composite component and the composite component. Background Art

[0002] Patent document 1 discloses a method for manufacturing a composite component. In this method, a composite component is manufactured by bonding a base material to a resin component. Micron-level or nanometer-level concavities and convexities are formed on the surface of the base material. By allowing the resin component to enter the micron-level or nanometer-level concavities and convexities and solidify, a stronger anchoring effect is produced compared to the case of millimeter-level concavities and convexities. Therefore, the composite component manufactured by this method has excellent bonding strength.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2017 / 141381 Summary of the invention

[0006] Compared with iron, aluminum is light and strong. Therefore, it is used as various parts and is also effective as a base material for composite components. The manufacturing method described in Patent Document 1 has room for improvement from the perspective of further improving the bonding strength of composite components using aluminum as a base material.

[0007] According to one aspect of the present invention, a method for manufacturing a composite component that joins an aluminum component to a resin component can be provided. The manufacturing method includes a sandblasting process, a surface hydrogen oxidation process, and a joining process. In the sandblasting process, the surface of the aluminum component is sandblasted. In the surface hydrogen oxidation process, at least one of heat and plasma is used to react the surface of the aluminum component that has been sandblasted with water to modify the surface of the aluminum component to aluminum hydroxide. In the joining process, the resin component is directly joined to the surface of the aluminum component that has been modified to aluminum hydroxide.

[0008] According to the manufacturing method, the surface of the aluminum component is sandblasted. Concavities and convexities are formed on the surface of the aluminum component after sandblasting. The concavities and convexities contribute to the anchoring effect. However, the concavities and convexities are formed by the collision of the spray material, and therefore become sharp-angled protrusions. The sharp-angled protrusions may become the starting point of the fracture of the resin component. According to the manufacturing method, the surface of the aluminum component after sandblasting is modified into aluminum hydroxide. As a result, the sharp-angled protrusions are rounded. Then, the resin component is directly bonded to the surface of the aluminum component modified into aluminum hydroxide. The resin component enters the rounded concavities and convexities and solidifies. In this way, according to the manufacturing method, since the sharp-angled protrusions that may become the starting point of the fracture of the resin component can be removed by the surface hydrogen oxidation process, the bonding strength of the composite component can be improved. Furthermore, in the surface of the aluminum component, the oxygen atoms of the hydroxyl group of the aluminum hydroxide are hydrogen-bonded with the hydrogen atoms contained in the resin. Therefore, since chemical bonds are generated between the surface of the aluminum component and the resin component, the bonding strength can be improved. Furthermore, the surface of the aluminum component composed of aluminum hydroxide has pores of tens to hundreds of nanometers. Therefore, the anchoring effect can be enhanced.

[0009] In one embodiment, the aluminum hydroxide may be boehmite.

[0010] In one embodiment, in the surface oxidation process, the surface of the aluminum component can be cleaned with water, and the surface of the aluminum component can be modified into aluminum hydroxide. When carbon contamination exists on the surface of the aluminum component, there is a concern that the wettability of the resin raw material is reduced and the chemical bond between the surface of the aluminum component and the resin component is hindered. According to this configuration, since the surface of the aluminum component is cleaned with water used when modifying into aluminum hydroxide, the reduction in bonding strength caused by carbon contamination can be suppressed.

[0011] In one embodiment, the surface hydrogen oxidation step may use any of hydrothermal treatment, steam treatment, superheated water vapor treatment, liquid phase plasma, and atmospheric pressure plasma mixed with water to react the surface of the aluminum member with water. The surface modification of the aluminum member can be achieved by the above treatments.

[0012] In one embodiment, the particle size of the abrasive grains used in the sandblasting process may be 30 μm to 710 μm. This can appropriately remove the oxide film formed on the surface of the aluminum member, thereby forming a uniform aluminum hydroxide film on the surface of the aluminum member.

[0013] According to another aspect of the present invention, there is provided a composite member including: an aluminum member having irregularities on its surface and having an aluminum hydroxide film formed on the surface; and a resin member in direct contact with the surface of the aluminum member having the aluminum hydroxide film formed thereon.

[0014] In this composite component, since the surface of the aluminum component in direct contact with the resin component has unevenness, an anchoring effect is exerted. In addition, an aluminum hydroxide film is formed on the surface of the aluminum component. The oxygen atoms of the hydroxyl groups of the aluminum hydroxide film are hydrogen-bonded with the hydrogen atoms contained in the resin. Therefore, a chemical bond is generated between the surface of the aluminum component and the resin component, so the bonding strength can be improved. In addition, the surface of the aluminum component formed with the aluminum hydroxide film has pores of tens to hundreds of nanometers. Therefore, the anchoring effect can be enhanced.

[0015] In one embodiment, the aluminum hydroxide membrane may be composed of boehmite.

[0016] According to an aspect and embodiments of the present invention, a method of manufacturing a composite member having excellent bonding strength and a composite member having excellent bonding strength may be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a perspective view showing a composite member according to the embodiment.

[0018] Figure 2 It is along Figure 1 Cross-sectional view of the composite component along line II-II.

[0019] Figure 3 This is a conceptual diagram of a sandblasting device used in the method for manufacturing a composite member according to an embodiment.

[0020] Figure 4 This is a diagram for explaining the configuration of a sandblasting device used in the method for producing a composite member according to the embodiment.

[0021] Figure 5 yes Figure 4 Cross-sectional view of the injection nozzle.

[0022] Figure 6 A top view of a mold used in injection molding.

[0023] Figure 7 It is along Figure 6 Cross-sectional view of the mold along line VII-VII.

[0024] Figure 8 This is a flowchart of a method for manufacturing a composite member according to an embodiment.

[0025] Fig. 9 This is a conceptual diagram of sandblasting.

[0026] Fig.10 This is a diagram for explaining scanning of the sandblasting process.

[0027] Fig.11 This is a diagram for explaining the manufacturing process of the composite member.

[0028] Fig.12 This is the surface observation result of the aluminum component.

[0029] Fig.13 This is the result of composition analysis of the surface of the aluminum component.

[0030] Fig.14 It is the result of shear strength measurement.

[0031] Explanation of symbols

[0032] 1...composite member, 2...aluminum member, 3...resin member, 10...sandblasting device, 11...processing chamber, 12...injection nozzle, 13...storage tank, 14...pressurization chamber, 15...compressed gas supply machine, 16...quantitative supply unit, 17...connecting pipe, 18...processing table, 19...control unit, 20...mold, 21...mold body. DETAILED DESCRIPTION

[0033] Hereinafter, the embodiment will be described with reference to the accompanying drawings. It should be noted that in the following description, the same or equivalent elements are denoted by the same reference numerals, and repeated descriptions are omitted. In addition, the "joining strength" of this embodiment is described as "shear strength".

[0034] [Composite components]

[0035] Figure 1 1 is a perspective view showing a composite member 1 according to an embodiment. Figure 1 As shown, the composite member 1 is a member in which a plurality of members are joined to form an integrated structure. For example, the composite member 1 is a member in which a resin member is joined to a member of a different type relative to the resin member. The member of a different type relative to the resin member is a member formed of a material having different properties such as thermal expansion coefficient, thermal conductivity, and strength relative to the resin member.

[0036] The composite member 1 includes an aluminum member 2 and a resin member 3. An example of the aluminum member 2 is a plate-shaped member. The resin member 3 is in direct contact with the surface of the aluminum member 2. Figure 1 In the embodiment, the resin member 3 is in direct contact with a part of the surface of the aluminum member 2 (the contact surface 4 of the aluminum member 2), and has an overlapping joint structure. The material of the aluminum member 2 is aluminum or an aluminum alloy. The material of the resin member 3 is a resin such as polybutylene terephthalate, polyphenylene sulfide, polyamide, liquid crystal polymer, polypropylene, acrylonitrile butadiene styrene, etc.

[0037] Figure 2 It is along Figure 1 A cross-sectional view of the composite member 1 taken along line II-II. Figure 2As shown, the aluminum component 2 has a concave-convex 2b on a part of its surface 2a (contact surface 4). The concave-convex 2b is a micrometer-level or nanometer-level concave-convex. The micrometer-level concave-convex is a concave-convex with a height difference of 1 μm or more and less than 1000 μm. The nanometer-level concave-convex is a concave-convex with a height difference of 1 nm or more and less than 1000 nm. The end of the concave-convex 2b is chamfered. Therefore, the concave-convex 2b has roundness and does not have a sharp angle. The resin component 3 is fixed by entering the concave-convex 2b, thereby exerting an anchoring effect.

[0038] Furthermore, an aluminum hydroxide film 2d is formed on the surface of the aluminum member 2. The aluminum hydroxide film 2d is a film composed of aluminum hydroxide, and has pores of several tens to several hundreds of nm on its surface. Aluminum hydroxide is a compound of aluminum having a hydroxyl group. The aluminum hydroxide film 2d is composed of boehmite as an example. In addition to boehmite, the aluminum hydroxide film 2d may also contain other aluminum hydroxides such as aluminum hydroxide and γ-alumina.

[0039] The resin member 3 is bonded to the aluminum member 2 in a state where a portion of the resin member 3 enters the concavo-convex 2b. Such a structure is formed by injection molding using a mold 20 described later. It should be noted that the composite member 1 can be bonded by a method other than injection molding, such as press molding, vibration bonding, ultrasonic bonding, etc.

[0040] Thus, the composite member 1 of the present embodiment has an anchoring effect because the surface 2a of the aluminum member 2 that is in direct contact with the resin member 3 has the unevenness 2b. In addition, an aluminum hydroxide film 2d is formed on the surface 2a of the aluminum member 2. The oxygen atoms of the hydroxyl groups of the aluminum hydroxide film 2d are hydrogen-bonded with the hydrogen atoms contained in the resin. Therefore, since a chemical bond is generated between the surface 2a of the aluminum member 2 and the resin member 3, the bonding strength can be improved. In addition, since the surface 2a of the aluminum member 2 formed with the aluminum hydroxide film 2d has pores of tens to hundreds of nanometers, the anchoring effect can be enhanced. Therefore, the composite member 1 has excellent bonding strength.

[0041] [Method for manufacturing composite member]

[0042] The apparatus used in the manufacturing method of the composite member 1 is briefly described. First, the apparatus for performing sandblasting on the surface of the aluminum member 2 is described. The sandblasting apparatus can use any type of gravity (suction) air sandblasting apparatus, direct pressure (pressurization) air sandblasting apparatus, centrifugal sandblasting apparatus, etc. The manufacturing method of this embodiment uses a so-called direct pressure (pressurization) air sandblasting apparatus as an example. Figure 31 is a conceptual diagram of a blasting apparatus 10 used in the method for manufacturing a composite member 1. The blasting apparatus 10 includes a processing chamber 11, a jet nozzle 12, a storage tank 13, a pressurizing chamber 14, a compressed gas supply device 15, and a dust collector (not shown).

[0043] The processing chamber 11 contains a spray nozzle 12, and the workpiece (here, the aluminum member 2) is sandblasted in the processing chamber 11. The spray material sprayed by the spray nozzle 12 falls to the lower part of the processing chamber 11 together with the dust. The falling spray material is supplied to the storage tank 13, and the dust is supplied to the dust collector. The spray material stored in the storage tank 13 is supplied to the pressurized chamber 14, and the pressurized chamber 14 is pressurized by the compressed gas supply machine 15. The spray material stored in the pressurized chamber 14 is supplied to the spray nozzle 12 together with the compressed gas. In this way, the workpiece is sandblasted while the spray material is circulated.

[0044] Figure 4 This is a diagram for explaining the configuration of a sandblasting device 10 used in the method for producing the composite member 1 according to the embodiment. Figure 4 The sandblasting device 10 shown is Figure 3 The direct pressure sandblasting device shown in the figure. Figure 4 In FIG. 1 , a part of the wall surface of the processing chamber 11 is omitted and shown.

[0045] like Figure 4 As shown, the sandblasting device 10 comprises: a blasting material storage tank 13 and a pressurizing chamber 14 which are connected to a compressed gas supply machine 15 and form a closed structure; a quantitative supply unit 16 which is connected to the storage tank 13 in the pressurizing chamber 14; a spray nozzle 12 which is connected to the quantitative supply unit 16 via a connecting pipe 17; a processing table 18 which is movable while holding a workpiece under the spray nozzle 12; and a control unit 19.

[0046] The control unit 19 controls the components of the sandblasting device 10. The control unit 19 includes a display unit and a processing unit as an example. The processing unit is a general computer having a CPU and a storage unit, etc. The control unit 19 controls the supply amount of the compressed gas supply machine 15 that supplies compressed gas to the storage tank 13 and the pressurization chamber 14 respectively based on the set injection pressure and injection speed. In addition, the control unit 19 controls the injection position of the injection nozzle 12 based on the set distance between the workpiece and the nozzle and the scanning conditions of the workpiece (speed, transfer spacing, number of scans, etc.). As a specific example, the control unit 19 controls the position of the injection nozzle 12 using the scanning speed (X direction) and transfer spacing (Y direction) set before the sandblasting process. The control unit 19 controls the position of the injection nozzle 12 by moving the processing table 18 that holds the workpiece.

[0047] Figure 5 yes Figure 4 sectional view of the injection nozzle 12. The injection nozzle 12 has a injection pipe holder 120 as a main body. The injection pipe holder 120 is a cylindrical member having a space inside for allowing the injection material and the compressed gas to pass. One end of the injection pipe holder 120 is an injection material inlet 123, and the other end is an injection material outlet 122. An inner wall surface whose front end tapers from the injection material inlet 123 side toward the injection material outlet 122 is formed inside the injection pipe holder 120, forming a conical contraction acceleration portion 121 with an inclined angle. A cylindrical injection pipe 124 is connected to the injection material outlet 122 side of the injection pipe holder 120. The contraction acceleration portion 121 tapers from the middle of the cylindrical portion of the injection pipe holder 120 toward the injection pipe 124 and the front end tapers. Thus, a compressed gas flow 115 is formed.

[0048] The connection pipe 17 of the blasting device 10 is connected to the blasting material introduction port 123 of the blasting nozzle 12. Thus, a blasting material path is formed in which the storage tank 13, the quantitative supply unit 16 in the pressurizing chamber 14, the connection pipe 17 and the blasting nozzle 12 are connected in sequence.

[0049] The sandblasting device 10 thus constructed supplies compressed gas of a supply amount controlled by the control unit 19 from the compressed gas supply machine 15 to the storage tank 13 and the pressurized chamber 14. Moreover, the injection material in the storage tank 13 is quantitatively supplied in the quantitative supply unit 16 in the pressurized chamber 14 by a constant pressure flow force, supplied to the injection nozzle 12 via the connecting pipe 17, and injected from the injection pipe of the injection nozzle 12 to the processing surface of the workpiece. Thus, a certain amount of injection material is always injected onto the processing surface of the workpiece. Moreover, the injection position of the injection nozzle 12 to the processing surface of the workpiece is controlled by the control unit 19, and the workpiece is sandblasted.

[0050] In addition, the injected abrasive material and the cutting powder generated during the sandblasting process are sucked by a dust collector (not shown). A classifier (not shown) is arranged on the path from the processing chamber 11 to the dust collector, and is separated into reusable abrasive material and other fine powder (abrasive material of a size that cannot be reused, and cutting powder generated during the sandblasting process). The reusable abrasive material is stored in the storage tank 13 and supplied to the injection nozzle 12 again. The fine powder is recovered by the dust collector.

[0051] Next, injection molding is described. As injection molding, insert molding is used here. In insert molding, an insert is installed in a predetermined mold, and resin is injected and held for a predetermined time to solidify. Then, the residual stress of the resin is removed by heat treatment. Figure 6 A top view of a mold used in injection molding. Figure 7 It is along Figure 6 The cross-sectional view of the mold along line VII-VII. Figure 6 , Figure 7 As shown, the mold 20 includes a mold body 21 (an upper mold 21a and a lower mold 21b). A space 22 for installing an insert (here, an aluminum component 2) and a space 23 for injecting resin are provided between the upper mold 21a and the lower mold 21b. A resin injection port is provided on the upper surface of the upper mold 21a. The resin injection port is connected to the space 23 via a runner 24, a runner 25 and a gate 26. A pressure sensor 27 and a temperature sensor 28 are provided in the space 23 to detect the pressure and temperature of the space 23. The parameters of the molding machine (not shown) are adjusted based on the detection results of the pressure sensor 27 and the temperature sensor 28 to manufacture a molded product. The parameters include mold temperature, resin temperature during filling, filling pressure, injection rate, holding time, pressure during holding, heat treatment temperature, heat treatment time, etc. The molded product molded by the mold 20 becomes an overlapping joint structure joined at a specified area.

[0052] Next, a series of steps of the method for producing the composite member 1 will be described. Figure 8 1 is a flow chart of a method MT for manufacturing a composite member 1 according to an embodiment. Figure 8 As shown, first, as a preparation process (S10), a predetermined shot blasting material is filled into the sandblasting device 10. The particle size of the shot blasting material (abrasive) is, for example, 30 μm to 710 μm. The smaller the particle size of the shot blasting material, the smaller the mass, and therefore, the inertial force becomes lower. Therefore, when the particle size of the shot blasting material is less than 30 μm, it is difficult to form the desired shape of the concave-convex 2b. In addition, the aluminum component 2 used in industry is generally stored in the atmosphere, and its surface is covered with an uneven non-crystalline aluminum oxide film with a thickness of 60 nm to 300 nm. Therefore, surface etching and surface laser processing using a reagent may become an uneven surface treatment due to the presence of the non-crystalline aluminum oxide film. In the surface hydrogen oxidation process described later, in order to uniformly modify the surface of the aluminum component 2, it is necessary to make the non-crystalline aluminum oxide film a film with a thickness of about 30 nm or less. However, when the particle size of the shot blasting material exceeds 710 μm, it is difficult to thin the non-crystalline aluminum oxide film to a thickness of about 30 nm or less. Therefore, the aluminum oxide formed on the surface of the aluminum component 2 cannot be fully removed. The particle size of the abrasive grains capable of achieving both the formation of the asperities and the removal of the amorphous oxide film of aluminum is 30 μm to 710 μm.

[0053] As a preparation process (S10), the control unit 19 of the sandblasting device 10 obtains the sandblasting conditions. The control unit 19 obtains the sandblasting conditions based on the operation of the operator or the information stored in the storage unit. The sandblasting conditions include the injection pressure, injection speed, the distance between nozzles, the scanning conditions of the workpiece (speed, transfer spacing, number of scans), etc. The injection pressure is, for example, 0.5 to 2.0 MPa. The smaller the injection pressure, the lower the inertia force. Therefore, when the injection pressure is less than 0.5 MPa, it is difficult to form the desired shape of the concave and convex 2b. The larger the injection pressure, the higher the inertia force. Therefore, the injection material is easily crushed due to the collision with the aluminum component 2. As a result, the following problems arise: (1) The energy of the collision is dispersed outside the formation of the concave and convex 2b, so the processing efficiency is poor, (2) The loss of the injection material is severe, which is not economical, etc. Such a phenomenon becomes significant when the injection pressure exceeds 2.0 MPa. The control unit 19 controls the size, depth, density, etc. of the concavo-convex 2b of the surface 2a of the aluminum member 2 precisely at the micrometer level or the nanometer level by managing the sandblasting conditions. In addition, the sandblasting conditions may also include conditions for determining the sandblasting target area. At this time, selective surface treatment can be performed.

[0054] Next, the sandblasting device 10 performs the following series of processes as a sandblasting process (S12). First, the aluminum component 2 to be sandblasted is placed on the processing table 18 in the processing chamber 11. Next, the control unit 19 operates the dust collector not shown. The dust collector reduces the pressure inside the processing chamber 11 to a negative pressure state based on the control signal of the control unit 19. Next, the injection nozzle 12 injects the injection material in the form of a solid-gas two-phase flow of compressed air within a range of injection pressure of 0.5 to 2.0 MPa based on the control signal of the control unit 19. Next, the control unit 19 operates the processing table 18 to move the aluminum component 2 into the injection flow of the solid-gas two-phase flow ( Figure 4 The center is below the spray nozzle). Fig. 9 This is a conceptual diagram of sandblasting. Fig. 9 As shown, the injection material is injected from the injection nozzle 12 toward a partial region 2c of the surface 2a of the aluminum member 2. Here, the control unit 19 continues to operate the processing table 18 to draw the aluminum member 2 with the injection stream in a preset trajectory. Fig.10 This is a diagram to explain the scanning of the sandblasting process. Fig.10 As shown, the control unit 19 operates according to the trajectory L of scanning the processing table 18 at the transfer pitch P. Thus, desired micron-level or nano-level concavities and convexities 2 b are formed on the surface of the aluminum member 2 .

[0055] By using a blasting material with a particle size of 30 to 710 μm and performing sandblasting at a blasting pressure range of 0.5 to 2.0 MPa, the desired micron-level or nanometer-level concavities and convexities 2b (for example, the concavities and convexities 2b with arithmetic mean slope RΔa and root mean square slope RΔq controlled to be 0.17 to 0.50 and 0.27 to 0.60, respectively) are formed on the surface 2a of the aluminum member 2. Furthermore, the amorphous oxide film on the surface of the aluminum member 2 becomes a film with a thickness of about 9 nm or less. After the operation of the sandblasting device 10 is stopped, the aluminum member 2 is taken out and the sandblasting is completed.

[0056] Fig.11 This is a diagram illustrating the manufacturing process of the composite member. Fig.11 As shown in (A), the irregularities 2b on the surface 2a of the aluminum member 2 after the sandblasting process have acute-angled protrusions.

[0057] Next, as a surface hydrogen oxidation step (S14), at least one of heat and plasma is used to make the surface 2a of the aluminum component 2 that has been sandblasted react with water, and the surface 2a of the aluminum component 2 is modified into aluminum hydroxide. In the surface hydrogen oxidation step, any one of hydrothermal treatment, water vapor treatment, superheated water vapor treatment, liquid phase plasma, and atmospheric pressure plasma mixed with water is used to make the surface 2a of the aluminum component 2 react with water. The following is an explanation of the case of using hydrothermal treatment as an example. In the hydrothermal treatment, the aluminum component 2 that has been sandblasted is immersed in pure water heated to above 70°C for a prescribed time. Thus, as Fig.11 As shown in (B), the concavo-convex 2b is rounded. Furthermore, the surface 2a of the aluminum component 2 is mainly modified into boehmite to form an aluminum hydroxide film 2d. In addition to boehmite, the aluminum hydroxide film 2d may also contain other aluminum hydroxides such as aluminum hydroxide and γ-alumina. It should be noted that in steam treatment, superheated water steam treatment, liquid phase plasma and atmospheric pressure plasma mixed with water, the temperature of the water only needs to be above 70°C. From the viewpoint of suppressing the material change of aluminum, the temperature of the water only needs to be below 300°C.

[0058] In the surface hydrogen oxidation process, the surface of the aluminum component can be cleaned with water. When the surface hydrogen oxidation process is performed by hydrothermal treatment, the surface of the aluminum component can be cleaned with water to reduce the surface carbon concentration. It should be noted that the surface carbon concentration can also be actively reduced by combining hydrothermal treatment and ultrasonic cleaning. For example, the aluminum component 2 is immersed in pure water heated to above 70°C and the pure water is irradiated with ultrasonic waves. Thus, hydrothermal treatment and surface cleaning can be performed simultaneously.

[0059] Next, as a joining process (S16), a molding machine (not shown) performs molding using the above-mentioned mold 20. First, the mold 20 is opened, the aluminum component 2 whose surface is modified to aluminum hydroxide is installed in the space 22, and the mold 20 is closed. Then, the molding machine injects the molten resin having a set resin temperature into the interior of the mold 20 from the resin injection port. The injected resin passes through the runner 24, the runner 25 and the gate 26 and fills the space 23. The molding machine controls the filling pressure and injection rate of the resin based on the detection result of the pressure sensor 27. The molding machine controls the mold temperature to a set value based on the detection result of the temperature sensor 28. In addition, the molding machine controls the pressure to a set value during the set holding time based on the detection result of the pressure sensor 27. Then, the molding machine performs heat treatment based on the set heat treatment temperature and heat treatment time. Then, the molding machine opens the mold 20 and takes out the composite component 1 in which the aluminum component 2 and the resin component 3 are integrated. When the joining process (S16) is completed, Figure 8 The flowchart shown ends. Fig.11 The composite component 1 shown in (C).

[0060] As described above, according to the manufacturing method MT, the surface 2a of the aluminum member 2 is sandblasted. The surface 2a of the aluminum member 2 after sandblasting is formed with a projection of an acute angle 2b. Then, the surface 2a of the aluminum member 2 after sandblasting is mainly modified to boehmite. As a result, the projection of the acute angle is rounded. Then, the resin member 3 is directly bonded to the surface 2a of the aluminum member 2 modified to aluminum hydroxide. The resin member 3 enters the rounded projection 2b and solidifies. In this way, according to the manufacturing method MT, since the projection of the acute angle that can become the starting point of the fracture of the resin member 3 can be removed by the surface hydrogen oxidation step (S14), the bonding strength of the composite member 1 can be improved. Furthermore, in the surface of the aluminum member 2, the oxygen atoms of the hydroxyl group of the boehmite are mainly hydrogen-bonded with the hydrogen atoms contained in the resin. Therefore, since a chemical bond is generated between the surface 2a of the aluminum member 2 and the resin member 3, the bonding strength can be improved. Moreover, the surface 2a of the aluminum member 2 mainly composed of boehmite has pores of tens to hundreds of nanometers. Therefore, the anchoring effect can be enhanced. In addition, the aluminum oxide film formed on the surface 2a of the aluminum member 2 is removed by sandblasting. The aluminum oxide film is a factor that hinders the formation of the aluminum hydroxide film 2d. According to the manufacturing method MT, since the aluminum oxide film is removed before the aluminum hydroxide is formed, the surface 2a of the aluminum member 2 can be modified into a homogeneous aluminum hydroxide.

[0061] According to the manufacturing method MT, since the surface 2a of the aluminum member 2 is cleaned by the water used in the modification of the aluminum hydroxide, the reduction in the bonding strength caused by the carbon contamination can be suppressed. According to the manufacturing method MT, by making the particle size of the abrasive used in the sandblasting process 30 μm to 710 μm, the oxide film formed on the surface 2a of the aluminum member 2 can be appropriately removed, so that a uniform boehmite film can be formed on the surface 2a of the aluminum member 2.

[0062] As mentioned above, although this embodiment was demonstrated, it is needless to say that this invention is not limited to this embodiment mentioned above, In addition to this embodiment, it can also be implemented with various deformation|transformation in the range which does not deviate from the summary.

[0063] [Modifications of base material and resin member]

[0064] As the aluminum member 2 and the resin member 3 of the above embodiment, a plate-shaped member is shown as an example, but it is not limited to this shape. All shapes that can contact each other can be adopted. In the above embodiment, the resin member 3 contacts a part of the surface of the aluminum member 2, but it can also contact the entire surface of the aluminum member 2.

[0065] [Variation of injection molding]

[0066] Injection molding is not limited to insert molding, but may also be outsert molding.

[0067] Example

[0068] [Abrasive particle size of blasting material]

[0069] First, the thickness of the oxide film of the aluminum component 2 before the sandblasting process (S12) is measured. The depth direction analysis of the aluminum oxide film is performed using "Auger electron spectroscopy (AES)". In order to simultaneously detect the oxide and metal components near the oxide / metal interface, they are separated by spectral synthesis to determine the thickness of the oxide film. The thickness of the oxide film is 72nm. Next, using Figure 3 to Figure 5 After the sandblasting process (S12) is performed by the sandblasting apparatus shown, the film thickness of the oxide film of the aluminum component 2 is measured. When the injection material with a center particle size of the abrasive grains of 600 μm to 710 μm is used, the film thickness of the oxide film is 13 nm. When the injection material with a center particle size of the abrasive grains of 41 μm to 50 μm (maximum particle size 127 μm or less, average particle size 57 μm ± 3 μm) is used, the film thickness of the oxide film is 9 nm. Therefore, it is confirmed that the oxide film on the surface 2a of the aluminum component 2 can be removed by using at least a injection material of 710 μm or less.

[0070] [Confirmation of the surface condition of aluminum components]

[0071] use Figure 3 to Figure 5 The sandblasting apparatus shown in the figure performs the sandblasting process (S12). Aluminum plates (JIS (Japanese Industrial Standards): A5052) are used for aluminum components. The material used for sandblasting is alumina, which is a blasting material with a center particle size of abrasive grains of 106 μm to 125 μm. The sandblasting pressure is 1.0 MPa. After the sandblasting process, a field emission scanning electron microscope (FE-SEM: Field Emission Scanning Electron Microscope) is used for surface observation.

[0072] Next, a surface hydrogen oxidation step ( S14 ) was performed. The sandblasted aluminum plate was immersed in pure water at 90° C. for 5 minutes. Then, the surface was observed using a field emission scanning electron microscope (FE-SEM).

[0073] Fig.12 This is the surface observation result of the aluminum component. Fig.12 (A) is the surface observation result of the aluminum plate after the sandblasting process (S12), Fig.12 (B) is the surface observation result of the aluminum plate after the surface oxidation process (S14). Fig.12 (C) and (E) are the surface observation results of the aluminum plate after the sandblasting process (S12). Fig.12 (D) and (F) are the results of surface observation of the aluminum plate after the surface hydrogen oxidation step (S14).

[0074] like Fig.12 As shown in (A) and (C), it is confirmed that the surface 2a of the aluminum member 2 after the sandblasting process (S12) is formed with unevenness and protrusions with sharp angles. Fig.12 As shown in (B) and (D), it is confirmed that the surface 2a of the aluminum member 2 after the sandblasting process (S12) has roundness as a whole. Fig.12 Comparison of (E) and (F) revealed that pores of several tens to several hundreds of nanometers were confirmed to exist on the surface of the aluminum plate after the surface hydrogenation step (S14).

[0075] [Confirmation of the composition of the surface of aluminum components]

[0076] [Example: Surface treated product]

[0077] use Figure 3 to Figure 5The sandblasting device shown implements the sandblasting process (S12). Aluminum plates (JIS: A5052) are used for aluminum components. The material used for sandblasting is alumina and the abrasive center particle size is 106μm to 125μm. The sandblasting pressure is 1.0MPa. Next, a surface hydrogen oxidation process (S14) is implemented. The aluminum plate that has been sandblasted is immersed in pure water at 90°C for 5 minutes.

[0078] [Comparative example: untreated product]

[0079] An aluminum plate (JIS: A5052) was used which had not been subjected to the sandblasting step (S12) and the surface hydrogen oxidation step (S14).

[0080] The surface composition of the surface treated and untreated products was analyzed by total reflectance measurement (ATR) using a Fourier transform infrared spectrophotometer (FT-IR). The analysis results are shown in Fig.13 .

[0081] Fig.13 This is the result of composition analysis on the surface of aluminum components. Fig.13 The coordinate graph shown in the figure has the wave number on the horizontal axis and the absorbance on the vertical axis. The waveform data shown above the coordinate graph is the composition analysis result of the surface treated product, and the waveform data shown below the coordinate graph is the composition analysis result of the untreated product. Fig.13 As shown in the waveform data of the unprocessed product, at wave number 3960m -1 、3930m -1 、2873m -1 A peak caused by carbon pollution (C-H, etc.) appears at wave number 946m -1 A peak due to aluminum oxide (Al-O) appeared at 3268 nm. No peak due to boehmite was confirmed. In contrast, in the data of the surface treated product, the peak due to carbon contamination (C-H, etc.) and the peak due to aluminum oxide (Al-O) that existed before treatment disappeared. -1 、3113m -1 Thus, it was confirmed that the oxides and carbon contaminants on the surface of the aluminum member 2 were removed by the surface treatment, and aluminum hydroxide was formed.

[0082] [Confirmation of surface carbon concentration]

[0083] The surface carbon concentration of the aluminum component 2 subjected to the surface hydrogen oxidation step (S14) and the surface carbon concentration of the untreated product were measured and compared. The measurement was performed using X-ray photoelectron spectroscopy (XPS). As a result, the surface carbon concentration of the untreated product was 40 at%, while the surface carbon concentration of the aluminum component 2 subjected to the surface hydrogen oxidation step (S14) was 8 at%. In this way, it was confirmed that the hydrothermal treatment had a cleaning effect as a secondary effect.

[0084] [Confirmation of shear strength]

[0085] Examples and Comparative Examples 1 to 3 were prepared to confirm the shear strength.

[0086] [Example]

[0087] use Figure 3 to Figure 5 The sandblasting device shown is used to implement the sandblasting process (S12). Aluminum plates (JIS: A5052) are used for aluminum components. The material used for sandblasting is alumina and the abrasive center particle size is 106μm to 125μm. The sandblasting pressure is 1.0MPa. Next, the surface hydrogen oxidation process (S14) is implemented. The sandblasted aluminum plate is immersed in pure water at 90°C for 5 minutes. Next, the bonding process (S16) is implemented. Use Figure 6 and Figure 7 The mold 20 shown joins the resin component 3 to the aluminum component 2. The resin component 3 is set in a manner that the length, width and thickness are 10mm×45mm×3.0mm. Polyphenylene sulfide resin (PPS) is used as the material of the resin component 3. As the resin component 3, three PPS with different components are prepared. During injection, the mold temperature is 150°C, the injection speed is 20mm / s, the injection pressure is 53~93MPa, and the injection time is 0.56s. During holding, the holding pressure is 80MPa and the holding time is 8s. The overlap between the aluminum component 2 and the resin component 3 is 5mm.

[0088] [Comparative Examples 1 to 3]

[0089] In Comparative Example 1, an aluminum plate (JIS: A5052) which was not subjected to the sandblasting step (S12) and the surface hydrogen oxidation step (S14) was prepared as a member. The joining step (S16) was the same as that of the example.

[0090] In Comparative Example 2, an aluminum plate (JIS: A5052) was used as the aluminum member without the sandblasting step (S12) and was subjected to the same surface hydrogen oxidation step (S14) as in the example. The joining step (S16) was the same as in the example.

[0091] In Comparative Example 3, an aluminum plate (JIS: A5052) was used as the aluminum member, which was subjected to the same sandblasting step (S12) as in the example and not subjected to the surface hydrogen oxidation step (S14). The joining step (S16) was the same as in the example.

[0092] [Joint strength evaluation]

[0093] The shear strength of Examples and Comparative Examples 1 to 3 produced under the above conditions was measured. The evaluation device was measured by a test method in accordance with ISO 19095. The measurement results are shown in Fig.14 .

[0094] Fig.14 The shear strength is measured as follows. Fig.14 As shown, three PPS with different components were joined in each of the embodiment and comparative examples 1 to 3, and the shear strengths of each were measured. The shear strengths of comparative example 1 were "0.0", "0.5", and "0.0", the shear strengths of comparative example 2 were "0.0", "0.4", and "0.6", the shear strengths of comparative example 3 were "5.5", "7.2", and "12.8", and the shear strengths of the embodiment were "12.2", "26.9", and "20.2".

[0095] By comparing Comparative Example 1 with Comparative Example 2, it can be confirmed that when only the surface hydrogen oxidation process (S14) is implemented, it does not significantly contribute to the improvement of shear strength. By comparing Comparative Example 1 with Comparative Example 3, it can be confirmed that the sandblasting process (S12) contributes to the improvement of shear strength. By comparing the embodiment with Comparative Examples 1 to 3, it can be confirmed that the combination of the sandblasting process (S12) and the surface hydrogen oxidation process (S14) significantly contributes to the improvement of shear strength. In addition, the results of the three types of PPS all show the above-mentioned trend. Therefore, it can be confirmed that the combination of the sandblasting process (S12) and the surface hydrogen oxidation process (S14) significantly contributes to the improvement of shear strength regardless of the material of the resin component 3.

Claims

1. A method for manufacturing a composite member, which is a method for manufacturing a composite member by bonding an aluminum member and a resin member, comprising the following steps: The sandblasting process is to sandblast the surface of the aluminum component. a surface hydrogen oxidation step of reacting the surface of the aluminum member processed by the sandblasting with water using liquid phase plasma or atmospheric pressure plasma mixed with water to modify the surface of the aluminum member into aluminum hydroxide; and A bonding step of directly bonding the resin member to the surface of the aluminum member modified into the aluminum hydroxide; In the surface hydrogen oxidation step, ultrasonic waves are applied to water.

2. The method for manufacturing a composite member according to claim 1, wherein: The aluminum hydroxide is boehmite.

3. The method for manufacturing a composite member according to claim 1 or 2, wherein: In the surface hydrogen oxidation step, the surface of the aluminum member is cleaned with the water, and the surface of the aluminum member is modified into the aluminum hydroxide.

4. The method for manufacturing a composite member according to claim 1 or 2, wherein: The particle size of the abrasive grains used in the sandblasting step is 30 μm to 710 μm.

Citation Information

Patent Citations

  • Production method for composite member, and composite member

    WO2017141381A1

  • Aluminium / resin composite exhibiting excellent weather resistance and manufacturing method for the same

    CN102652058A

  • Production method for composite member, and composite member

    CN108698272A